Avoiding regeneration with a matrix converter drive - Munuswamy, Imayavaramban (2009)
Recently, the conventional Matrix Converter has been considered for aerospace applications because of its compactness in weight and size due to absence of a DC-Link capacitor. In addition the Matrix Converter is capable of producing a variable output voltage with unrestricted input and output frequency. This is useful in aerospace applications which require a wide range of input frequency, sometimes from 360 Hz to 900 Hz. These key features are only obtained from the Matrix Converter without using any large passive components. The Matrix Converter has an inherent regeneration capability. However, the avoidance of the regeneration may be vital in many aerospace applications, such as aircraft surface actuation systems. According to current aircraft power quality specifications regeneration is not allowed and must be dissipated with in the Matrix Converter drive itself.